(untitled) (Research, Society and Development, 2021)
This work aims to carry out a literature review on the main behavioral changes in cats, discussing in an objective and clear way their possible causes, forms of prevention and treatment, as well as a brief summary of the basic needs for well-being of the domestic feline. A narrative review was carried out, using scientific articles, monographs, theses and dissertations published and available in online databases: Periodical Capes (Coordination for the Improvement of Higher Education Personnel), SciELO (Scientific Electronic Library Online) and Google Scholar, in addition to specific books on the topic. Aggression was the most studied and discussed change related to cat behavior in the consulted literature, followed by scratching in unacceptable places and elimination in inappropriate places. It was observed that the neglect of the basic needs of felines is the main cause of behavioral changes and that guardians should be made aware of the food, management and environmental needs of pet cats. It is noteworthy that the proactive approach of the veterinarian is of fundamental importance, notably in the process of raising awareness of the tutor, in teaching about proper management, about environmental enrichment and in the search for undiagnosed diseases, in order to minimize disorders related to the feline behavior, abandonment and euthanasia.